2004
DOI: 10.1016/j.jhsb.2004.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis and Altered expression of Intercellular Adhesion Molecule-1 (Icam-1) after Avulsion Injury in Rat Vessels

Abstract: This study was undertaken to characterize the relative degrees of arterial and venous trauma after graded avulsion injuries. Rat femoral arteries and veins were subjected to reproducible avulsion injuries using forces of between 60 and 220g. Thrombotic occlusion occurred at lower avulsion forces in veins than in arteries. Histologic and scanning electron microscopic analysis indicated increased endothelial disruption and exposed elastic lamina with increasing avulsion force in both vessels, but more prominentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Once stimulated, the endothelial cell undergoes a number of morphological changes, including increased surface expression of adhesion molecules, cytoskeletal reorganization, and activation of signaling pathways (5,17,37). A strong and repeatable correlation between induction of ICAM-1 and increased BBB permeability has been shown in a number of pathologies characterized by acute inflammation, including atherosclerosis, ischemia, human immunodeficiency virus encephalitis, and autoimmune disorders (4,19,38,47). Furthermore, loss of endothelial cell, tight junction proteins, occludin, and zonula occludens-1 was observed in cerebral vascular endothelium during neutrophil-induced BBB breakdown (1).…”
mentioning
confidence: 99%
“…Once stimulated, the endothelial cell undergoes a number of morphological changes, including increased surface expression of adhesion molecules, cytoskeletal reorganization, and activation of signaling pathways (5,17,37). A strong and repeatable correlation between induction of ICAM-1 and increased BBB permeability has been shown in a number of pathologies characterized by acute inflammation, including atherosclerosis, ischemia, human immunodeficiency virus encephalitis, and autoimmune disorders (4,19,38,47). Furthermore, loss of endothelial cell, tight junction proteins, occludin, and zonula occludens-1 was observed in cerebral vascular endothelium during neutrophil-induced BBB breakdown (1).…”
mentioning
confidence: 99%
“…Vessels treated with SDF-1α showed less thrombosis adhering to the denuded vascular intima (►Fig. 5).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…[1][2][3][4] Although there are multiple causes for failure of microsurgical anastomosis, intimal injury plays a critical role. 5 It has been demonstrated that end-to-end anastomosis results in widespread loss of intima. 6 Loss of intima following microsurgical anastomosis leads to exposure of subendothelial tissue and release of tissue factor, which initiates the process of thrombosis formation.…”
mentioning
confidence: 99%
“…Molekul adhesi yang bersirkulasi, seperti soluble intercellular adhesion molecule-1 (sVCAM-1) dan soluble vascular cell adhesion molecule-1 (sVCAM-1), telah terbukti meningkat pada pasien dengan SM. 7 Beberapa penelitian telah memaparkan asosiasi ICAM-1 dan VCAM-1 dengan proses dan kejadian trombosis [8][9][10] , namun belum pernah diteliti hubungan ICAM-1 dan VCAM-1 dengan trombosis atrium kiri pada SM. Pada perempuan.…”
Section: Penilaian Gradasi Trombosisunclassified